Optimal investment of renewable energy to achieve sustainable regional development in the Kingdom of Saudi Arabia according to Vision 2030 - Alzhrani, Ashwag Mohammed; Al-Jasser, Lamia AbdulAziz (Journal of Humanities & Social Sciences, 2022)
This study dealt with the optimal investment of renewable energy to achieve sustainable regional development in the Kingdom of Saudi Arabia according to Vision 2030, and aimed to identify renewable energy and its various sources, and its relationship to both environment and development, and to see indicators of renewable energy in the Kingdom of Saudi Arabia and its progress, and the study relied on the approach descriptive and analytical, and reached several results, including that the Kingdom enjoys a distinct geographical and climatic location that makes benefiting from renewable energy sources economically feasible and supportive of its efforts in the field of diversifying energy sources. The study recommended that in order for the Kingdom to reach the goal it seeks, it must attach importance to the growth of the sector through the participation of the private sector, attracting foreign direct investment, creating job opportunities and localizing local output and content.